Australia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper and Statistical Appendix focuses on two analytical approaches for judging whether the current account for Australia is sustainable. The paper implements the first approach, by asking how Australia's net external liability position is likely to evolve over time, based on assumptions of future growth and interest rates. The paper implements the second approach by exploring the implications of a model of optimal external borrowing and lending. The main conclusions are also discussed in the paper.